Influence of treatment with neutralizing monoclonal antibodies on the SARS-CoV-2 nasopharyngeal load and quasispecies. (January 2022) - Vellas, Camille; Del Bello, Arnaud; Debard, Alexa; Steinmeyer, Zara; Tribaudeau, Laure; Ranger, Noémie; Jeanne, Nicolas; Martin-Blondel, Guillaume; Delobel, Pierre; Kamar, Nassim; Izopet, Jacques
Abstract: Objectives: To evaluate the impact of neutralizing monoclonal antibody (mAb) treatment and to determine whether the selective pressure of mAbs could facilitate the proliferation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with spike protein mutations that might attenuate mAb effectiveness. Patients and methods: We evaluated the impact of mAbs on the nasopharyngeal (NP) viral load and virus quasispecies of mAb-treated patients using single-molecule real-time sequencing. The mAbs used were: Bamlanivimab alone (four patients), Bamlanivimab/Etesevimab (23 patients) and Casirivimab/Imdevimab (five patients). Results: The NP SARS-CoV-2 viral load of mAb-treated patients decreased from 8.2 log10 copies/mL before administration to 4.3 log10 copies/mL 7 days after administration. Five immunocompromised patients given Bamlanivimab/Etesevimab were found to have mAb activity-reducing spike mutations. Two patients harboured SARS-CoV-2 variants with a Q493R spike mutation 7 days after administration, as did a third patient 14 days after administration. The fourth patient harboured a variant with a Q493K spike mutation 7 days post-treatment, and the fifth patient had a variant with a E484K spike mutation on day 21. The emergence of the spike mutation was accompanied by stabilization or rebound of the NP viral load in three of five patients. Conclusion: Two-mAb therapy can drive the selection of resistant SARS-CoV-2 variants in immunocompromised patients. Patients given mAbs should be closely monitored and measures to limit virus spread should be reinforced.